Individual vs. group-based strategies for weight loss and management in adults: Pen profile perceptions. (June 2020) - Clark, Cain C.T.; Chambers, Amie; Fernandes, John F.T.; Musalek, Martin; Podstawski, Robert; Eyre, Emma L.J.; Duncan, Michael
Abstract: Aims: The aim of this study was to explore perceptions of barriers, facilitators, strategies and successes in individual vs. group-based weight management programmes. Methods: Forty-two, overweight (Body Mass Index ≥ 25-kg . m 2 ) participants (aged 32-63y) volunteered to take part in this study. All participants completed a 3-month weight loss programme, randomised to a group-based (n = 21), or self-monitoring only (n = 21) approach, respectively. Participants subsequently participated in a semi-structured interview (60 ± 7 min) to explore individual and collective perceptions of barriers, facilitators, strategies and successes. Results: Convergent themes were found for individual and group strategies for facilitators, strategies and successes. Divergent themes were found between groups for barriers, group participants highlighted expense of commercial products, and knowledge of nutrition and dieting, whilst individual participants reported (lack of) social support from peers, (lack of) motivation, and occupation. Conclusion: Key stakeholders, facilitators, and individuals must consider these factors prior to the advocation any weight loss strategy. Highlights: There is no one size fits all approach to weight-loss strategies. Facilitators for weight-loss are comparable whether group-based or individual only strategies. Barriers to weight-loss vary between group-based and individual only strategies. The main barrier for group-based was associated expense and lacking knowledge. The main barrier for individual only was lack of social support and motivation.